Effective and Professional Management of Village Tourism Objects Through BUMDes: Pengelolaan Objek Wisata Desa yang Efektif dan Profesional Melalui BUMDes - Darmawan, Mochammad Ramli; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to analyze and describe the role of Village Owned Enterprises (BUMDes) in managing tourism objects in Sidokepung Village. The research is a qualitative study that focuses on the role of female village heads in empowering women. Data was collected through observation, interviews, and documentation, and analyzed using the data reduction, data presentation, and data verification proposed by Miles and Huberman. The results indicate that the motivator dimension in tourism management was not successful, the facilitator dimension was not optimal, and the Dynamisator was not implemented properly. The implications of these findings suggest that there is a need for improvement in the management of tourism objects in Sidokepung Village, particularly in the areas of motivation, facilitation, and dynamization. Highlight : Limited success: BUMDes management of tourism in Sidokepung fell short in motivating, facilitating, and dynamizing the sector. Female leadership focus: Research explored the specific role of female village heads in empowering women through tourism initiatives. Areas for improvement: Findings highlight the need for enhanced strategies in motivation, facilitation, and dynamization to boost tourism success Keywords: BUMDes, Sidokepung village, tourism, female leadership, women empowerment